Liquid ruralities: new identities versus old imaginaries. Contemporary art in rural Malaga - García-Pozuelo, Salvador (ARTxt. Artistic Experimentation Review, 2023)
Although in the collective imaginary there is still a vision of the rural debtor of the contributions of classical sociology, the life of the rural world and its inhabitants is already very different. The boundaries with the urban are increasingly diffuse, which generates a diverse rurality. For about a quindennium, the rural world has been arousing great interest. The manifestations of this trend are evident in all cultural and therefore artistic spheres. Rural Malaga would be a good example of the different ways to channel the growing relationship of rural peoples with contemporary art.